Calmodulin kinase II regulates atrial myocyte late sodium current, calcium handling and atrial arrhythmia - Greer-Short, Amara (Heart Rhythm, 2019)
BACKGROUND: Atrial fibrillation (AF) is the most common type of arrhythmia. Abnormal atrial myocyte Ca(2+) handling promotes aberrant membrane excitability and remodeling important for atrial arrhythmogenesis. The sequence of molecular events leading to loss of normal atrial myocyte Ca(2+) homeostasis is not established. Late Na(+) current (I(Na),(L)) is increased in atrial myocytes from AF patients together with an increase in activity of Ca(2+)/calmodulin-dependent kinase II (CaMKII). OBJECTIVE: To determine whether CaMKII-dependent phosphorylation at Ser571 on Na(v)1.5 increases atrial I(Na,L), leading to aberrant atrial Ca(2+) cycling, altered electrophysiology and increased AF risk. METHODS: Atrial myocyte electrophysiology, Ca(2+) handling, and arrhythmia susceptibility were studied in wildtype and Scn5a knock-in mice expressing phosphomimetic (S571E) or phosphoresistant (S571A) Na(v)1.5 at Ser571. RESULTS: Atrial myocytes from S571E but not S571A mice displayed an increase in I(Na,L) and action potential duration, and with adrenergic stress have increased DADs. Frequency of Ca(2+) sparks and waves was increased in S571E atrial myocytes compared to WT. S571E mice showed an increase in atrial events induced by adrenergic stress and AF inducibility in vivo. Isolated S571E atria were more susceptible to spontaneous atrial events, which were abrogated by inhibiting sarcoplasmic reticulum Ca(2+) release (RyR2), CaMKII, or the Na(+)/Ca(2+) exchanger. Expression of phospho-Na(v)1.5 at Ser571 and autophosphorylated CaMKII were increased in atrial samples from human AF patients. CONCLUSION: These studies identify CaMKII-dependent regulation of Na(v)1.5 as an important upstream event in Ca(2+) handling defects and abnormal impulse generation in the setting of AF.